CK2 Inhibition Prior to Status Epilepticus Persistently Enhances KCa2 Function in CA1 Which Slows Down Disease Progression - Schulze, Felix; Müller, Steffen; Guli, Xiati; Schumann, Lukas; Brehme, Hannes; Riffert, Till; Rohde, Marco; Goerss, Doreen; Rackow, Simone; Einsle, Anne; Kirschstein, Timo; Köhling, Rüdiger (Frontiers in Cellular Neuroscience, 2020)
Purpose: Epilepsy therapy is currently based on anti-seizure drugs that do not modify the course of the disease, i.e. they are not anti-epileptogenic in nature. Previously, we observed that in vivo casein kinase 2 (CK2) inhibition with 4,5,6,7-tetrabromotriazole (TBB) had anti-epileptogenic effects in the acute epilepsy slice model. Methods: Here, we pretreated rats with TBB in vivo prior to the establishment of a pilocarpine-induced status epilepticus in order to analyze the long-term sequelae of such a preventive TBB administration. Results: We found that TBB pretreatment delayed onset of seizures after pilocarpine and slowed down disease progression during epileptogenesis. This was accompanied with a reduced proportion of burst firing neurons in the CA1 area. Western blot analyses demonstrated that CA1 tissue from TBB-pretreated epileptic animals contained significantly less CK2 than TBB-pretreated controls. On the transcriptional level, TBB pretreatment led to differential gene expression changes of KCa2.2, but also of HCN1 and HCN3 channels. Thus, in the presence of the HCN channel blocker ZD7288, pretreatment with TBB rescued the afterhyperpolarizing potential as well as spike frequency adaptation in epileptic animals, both of which are prominent functions of KCa2 channels. Conclusion: These data indicate that TBB pretreatment prior to status epilepticus slows down disease progression during epileptogenesis involving increased KCa2 function, probably due to a persistently decreased CK2 protein expression.